Unnatural Nucleotides: Exploring the Information Storage System of DNA - Yadav, Aarti; Khera, Khushi; Mehrotra, Rekha; Kaur, Kohinoor; Agrawal, Yamini; Srivastava, Pratima; Thakur, Suresh (Archives of Clinical and Biomedical Research, 2022)
The conventional genetic alphabet has been expanded now with the development of several synthetic unnatural base pairs. The unnatural base pairs formed by recognition and interaction of these unnatural bases are able to maintain the standard Watson and crick structure of DNA as well. Furthermore, these unnatural nucleotides developed by various groups have the ability to store and transcribe the information just like the natural DNA. The review describes the efficient replication, transcription and translation of Unnatural Base Pairs (UBPs) highlighting the possibility of the expanded genetic alphabets. The review also outlines the vast applications of UBPs as novel information storage components as well as in creation of semi-synthetic organisms expressing non canonical amino acids, high affinity aptamer generation, PCR based diagnostics and sitespecific labelling of RNAs.